Exploring and expanding the phenotype and genotype diversity in seven Chinese families with spondylo-epi-metaphyseal dysplasia - Lv, Shanshan; Zhao, Jiao; Liu, Li; Wang, Chun; Yue, Hua; Zhang, Hao; Li, Shanshan; Zhang, Zhenlin (Frontiers in Genetics, 2022)
Spondylo-epi-metaphyseal dysplasia (SEMD) is a heterogeneous group of disorders with different modes of inheritance and is characterized by disproportionate or proportionate short stature. To date, more than 30 disease-causing genes have been identified, and different types of SEMD exhibit greatly overlapping clinical features, which usually complicate the diagnosis. This study was performed to expand the clinical and molecular spectrum of SEMD among Chinese subjects and to explore their potential phenotype–genotype relations. We enrolled seven families including 11 affected patients with SEMD, and their clinical, radiographic, and genetic data were carefully analyzed. All the seven probands showed different degrees of short stature, and each of them exhibited additional specific skeletal manifestations; four probands had extraosseous manifestations. X-rays of the seven probands showed common features of SEMD, including vertebral deformities, irregular shape of the epiphysis, and disorganization of the metaphysis. Seven variants were identified in TRPV4 (c.694C> T, p.Arg232Cys), COL2A1 (c.654 + 1G > C; c.3266_3268del, p.Gly1089del), CCN6 (c.396 T> G, p.Cys132Trp; c.721 T>C, p.Cys241Arg), SBDS (c.258 + 2T> C), and ACAN (c.1508C> A, p.Thr503Lys) genes, and two of them were novel. Two families with TRPV4 variants showed considerable intrafamily and interfamily heterogeneities. In addition, we reported one case of SEMD with a severe phenotype caused by ACAN gene mutation. Our study expands the phenotype and genetic spectrum of SEMD and provides evidence for the phenotype–genotype relations, aiding future molecular and clinical diagnosis as well as procreative management of SEMD.